Organizational Justice and Readiness for Change: A Concomitant Examination of the Mediating Role of Perceived Organizational Support and Identification - Arnéguy, Elodie; Ohana, Marc; Stinglhamber, Florence (Frontiers in Psychology, 2018)
Survival in today’s global economy requires organizations to be flexible and adapt readily to the ever-changing marketplace. However, more than 70% of organizational change initiatives fail, mostly due to employees’ resistance to change. The literature has identified readiness for change (RFC) as an important cognitive precursor of resistance. A body of research has accordingly investigated the determinants of employees’ RFC. In particular, RFC has been shown to be positively predicted by employees’ perceptions of fair treatment. Little is known, however, on the mechanisms underlying this relationship. Relying on social exchange theory and social identity theory, this paper investigates the concomitant mediating role of perceived organizational support (POS) and organizational identification (OID) between overall justice and RFC. One hundred and forty-five employees of a company located in France participated in a survey-based study. Results of the path analyses indicated that POS mediates the positive effect of organizational justice on RFC, while OID does not act as a mediator in this relationship. As a whole, these results show the relevance of social exchange theory to better understand how employees become ready to change in organizational settings.